2016
DOI: 10.1139/apnm-2016-0226
|View full text |Cite
|
Sign up to set email alerts
|

Exercise prescription to reverse frailty

Abstract: Abstract:Frailty is a clinical geriatric syndrome caused by physiological deficits across multiple systems. These deficits make it challenging to sustain homeostasis required for the demands of everyday life. Exercise is likely the best therapy to reverse frailty status. Literature to date suggests that pre-frail older adults, those with 1-2 deficits on the Cardiovascular Health Study-Frailty Phenotype (CHS-frailty phenotype), should exercise 2-3 times a week, for 45-60 min. Aerobic, resistance, flexibility, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 29 publications
2
123
0
2
Order By: Relevance
“…Bray et al (Table 1) [14] recently proposed a literature based, structured exercise prescription for pre-frail and frail older adults that could be tested for efficacy among adult survivors of childhood cancer. This type of intervention is safe and has demonstrated preliminary efficacy to improve fitness in small samples of childhood sarcoma and ALL survivors.…”
Section: Potential Interventions For Fitness and Quality Of Life In Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Bray et al (Table 1) [14] recently proposed a literature based, structured exercise prescription for pre-frail and frail older adults that could be tested for efficacy among adult survivors of childhood cancer. This type of intervention is safe and has demonstrated preliminary efficacy to improve fitness in small samples of childhood sarcoma and ALL survivors.…”
Section: Potential Interventions For Fitness and Quality Of Life In Cmentioning
confidence: 99%
“…In older adults and in childhood cancer survivors, frailty, represented by a constellation of three or more of: low lean muscle mass, muscle weakness, slow walking speed, low energy expenditure, and/or self-reported exhaustion, is associated with new onset of chronic disease and mortality. Additionally, in older adults, and in persons with chronic disease, frailty is associated with diminished quality of life [10, 11, 12, 13], an association that is heightened among persons who also have depression [14]. The association between frailty and quality of life, and the additional potential contribution of depression to this association have not been investigated among adult survivors of childhood cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective interventions are often multicomponent and interdisciplinary programs that capitalize on the older adult's remaining assets. Recommendations for exercise (Bray et al 2016) and nutrition (Laur et al 2017) interventions are already reported within APNM.…”
Section: Why Is Exercise and Nutrition Research Important In Addressimentioning
confidence: 99%
“…The recommendations for exercise to reverse frailty (Bray et al 2016) provide evidence to support a targeted, multi-component exercise strategy based upon the individual's level of frailty or frailty phenotype. For example, older adults transitioning toward frailty often do not recognize the subtle changes (sarcopenia, dynapenia, osteopenia) that reduce lower leg strength and increase fall risk.…”
Section: Why Is Exercise and Nutrition Research Important In Addressimentioning
confidence: 99%